2015
DOI: 10.1116/1.4936384
|View full text |Cite
|
Sign up to set email alerts
|

Novel chemoresistive CH4 sensor with 10 ppm sensitivity based on multiwalled carbon nanotubes functionalized with SnO2 nanocrystals

Abstract: Chemoresistive sensors based on multiwalled carbon nanotubes (MWCNTs) functionalized with SnO2 nanocrystals (NCs) have great potential for detecting trace gases at low concentrations (single ppm levels) at room temperature, because the SnO2 nanocrystals act as active sites for the chemisorption of gas molecules, and carbon nanotubes (CNTs) act as an excellent current carrying platform, allowing the adsorption of gas on SnO2 to modulate the resistance of the CNTs. However, uniform conjugation of SnO2 NCs with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…We explored the relative resistance change for 10 ppm methane at two different RH levels. 26 While exposing the SnO 2 -MWCNT sensor to 10 ppm of CH 4 in dry air at the higher RH (approximately 70%), a monotonic resistance increment was observed which was similar to the low RH tests where RH was held constant at 5%, as seen in Fig. 8.…”
Section: B Methane Sensingsupporting
confidence: 63%
“…We explored the relative resistance change for 10 ppm methane at two different RH levels. 26 While exposing the SnO 2 -MWCNT sensor to 10 ppm of CH 4 in dry air at the higher RH (approximately 70%), a monotonic resistance increment was observed which was similar to the low RH tests where RH was held constant at 5%, as seen in Fig. 8.…”
Section: B Methane Sensingsupporting
confidence: 63%
“…However, the concentration of methane (CH 4 ) gas is increasing day by day due to green house effect. Several efforts have been done for the development of CH 4 gas sensors [47][48][49][50][51][52][53][54][55][56][57][58]. The detection of CH 4 with our proposed device for climatic and household applications can be considered as future work.…”
Section: Influence Of Oxygen and Water Molecules On The Current-voltamentioning
confidence: 99%
“…The films were robust, thin and could be integrated into flexible and transparent electronic applications. The sensor performed well at low concentrations, exhibiting limits of detection of 1 ppm for NO 2 and 7 ppm for NH 3 Finally, Humayun et al, [196] reported the fabrication of chemoresistive sensors based on SnO 2 nanocrystal functionalised MWCNTs for detecting CH 4 gas with 10 ppm limit of detection. The authors stated that the sensors sensitivity even for trace analytes, (single ppm level),coupled with its significant reversible relative resistance change, was directly related to the extent of successful functionalisation of the MWCNT surface by the SnO 2 nanocrystals, as no response was observed for CH 4 by un-functionalised MWCNT based probes.…”
Section: Cnt-based Gas Sensorsmentioning
confidence: 99%